Capacidade de resposta dos ??rg??os p??blicos aos acidentes ocorridos no transporte rodovi??rio de produtos perigosos na cidade de S??o Paulo - Haddad, Edson (2017)
S??o Paulo is the most industrialized city in Latin America with intense handling of chemical cargos, mostly by road. Thus, accidents during hazardous materials road transportation in the city of S??o Paulo can be expected, which is of great concern due to inherent chemicals dangers as toxicity, flammability and corrosivity and due to high urban population density. Fatalities or severe damages to people??s health as well as environmental impacts may result from chemical accidents. On the other hand, public agencies response capability can significantly interfere on the magnitude of impacts caused by chemical accidents in the city. Adequate response actions by public agencies might minimize accidental events consequences on people??s health and on the environment. This study purpose is to evaluate the current effective public agencies response capability to accidents that might to come about during hazardous materials road transportation in the city of S??o Paulo. To do so, a case study was carried out, which encompassed consequences simulation through mathematical models of a road accident involving a cylinder of 900 kg of liquid chlorine. Results, in terms of distances reached by toxic chlorine clouds, were plotted on an important road in the city of S??o Paulo, and were estimated the number of fatalities and intoxications that the event could cause on the people. The results were brought forward to five public agencies experts who usually take part on emergency response actions on a routine daily basis in the city of S??o Paulo, so that they can evaluate their response capability to the simulated scenario. Based on the simulations, on expert interviews and on documentation raised during the data collection stage, an analysis was carried out in order to consolidate the current response capability of public agencies to respond to road accidents involving hazardous materials in the city of S??o Paulo. As a result, several weaknesses of public agencies were identified, such as a high response time, lack of procedures, materials resources and hospital infrastructure, among others, and so it was concluded that public agencies are not prepared to deal with accidents with severe consequences on the people??s health during hazardous materials road transportation in the city of S??o Paulo.